COMPARATIVE ANALYSIS OF ISLAMIC BANK SOUNDNESS LEVEL - Nabila, Arfeni (Journal of Islam and Science, 2021)
The purpose of this study was to assess the soundness level of Bank Syariah Mandiri, Bank Muamalat Indonesia, and Bank Negara Indonesia Syariah using the RGEC method (Risk Profile, GCG, Earning, Capital) for the 2019 period. The method used is a descriptive research approach, with publication report data. Finance obtained from online media used by Banks with due observance of the RGEC method in the world of Islamic Banking. This study wants to reveal a comparison of the level of health in three Islamic banks. This research was conducted in a limited scope, in terms of GCG factors, data taken from annual reports so that further research data can be processed in the GCG factor in the form of data obtained from the results of questionnaires to bank stakeholders. The range of areas and types of methods used will be more varied with a more diverse sample of banks so as to provide more accurate conclusions. The results showed that Bank Syariah Mandiri, Bank Muamalat Indonesia and Bank Negara Indonesia Syariah as the state-owned banks with the largest assets received a very healthy CAR Composite Rating. This reflects the condition of the three banks which are considered highly capable of dealing with significant negative effects from changes in business conditions and other external factors, however if a weakness occurs, it can be said that in general these weaknesses are not significant even though seen from the ROA Composite Rating Value, Bank Muamalat Indonesia gets unhealthy rating with an ROA value of 0.05% based on Bank Indonesia Regulation No. 13/1/PBI/2011 concerning Assessment of the Soundness of Commercial Banks with Risk-Profile, Good Corporate Governance (GCG), Earnings, and Capital.